2012
DOI: 10.1017/s0954422412000054
|View full text |Cite
|
Sign up to set email alerts
|

Excess body fat in obese and normal-weight subjects

Abstract: Excess body adiposity, especially abdominal obesity and ectopic fat accumulation, are key risk factors in the development of a number of chronic diseases. The advent of in vivo imaging methodologies that allow direct assessment of total body fat and its distribution have been pivotal in this process. They have helped to identify a number of sub-phenotypes in the general population whose metabolic risk factors are not commensurate with their BMI. At least two such sub-phenotypes have been identified: subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(130 citation statements)
references
References 146 publications
2
113
0
6
Order By: Relevance
“…Furthermore, excess accumulation of ectopic fat in liver, skeletal muscle, and pancreas is known to contribute to metabolic disturbances [67]. For example, Ogorodnikova and his co-workers have reported that MHO women had intermediate levels of epicardial, pericardial and hepatic fat as compared to lean healthy and MUO women and were associated with insulin resistance [68].…”
Section: Challengesmentioning
confidence: 99%
“…Furthermore, excess accumulation of ectopic fat in liver, skeletal muscle, and pancreas is known to contribute to metabolic disturbances [67]. For example, Ogorodnikova and his co-workers have reported that MHO women had intermediate levels of epicardial, pericardial and hepatic fat as compared to lean healthy and MUO women and were associated with insulin resistance [68].…”
Section: Challengesmentioning
confidence: 99%
“…Indeed, a whole body 1 H MRS can be obtained in <1 second, leading generally to a spectrum consisting of just 2 peaks: water at 4.7 ppm and fat at 1.3 ppm, and the resulting analysis is simply their ratio, Figure 3. Compared to a whole body MRI scan, which requires significant analysis time (>30 mins), 1 H MRS of large data sets, with its rapid acquisition and analysis, becomes extremely attractive.…”
Section: Whole Body Adipositymentioning
confidence: 99%
“…To date there have been several validation studies of this technique on mice 19 and rats 21 , where body fat content measured using whole body 1 Thus, caution must be taken in interpreting the fat/water ratio obtained by 1 H-MRS, as changes in the fat content detected by this technique may be a consequence of real variations in fat content -or simply reflect changes due to increases in tissue hydration or edema. Interestingly, the very difference between MRS and MRI outputs could in theory be utilized to assess changes in AT hydration, although interpretation of the results may not be straight forward.…”
Section: <Figure 3 Near Here>mentioning
confidence: 99%
See 1 more Smart Citation
“…Central obesity measurments (such as waist circumference) are less influenced by the amount of LT, and more sensitive to the VAT-SAT distribution. However, within the range of normal waist circumferences there is still large variations in the VAT-SAT distribution, as has been demonstrated by Thomas et al [9]. There are many benefits of more accurate and precise body-composition methods, as they would allow more sensitive diagnosis and monitoring of intervention effects.…”
Section: Tomographic Body-composition Analysismentioning
confidence: 96%